Suara Perlawanan: Bagaimana Mahasiswa Menggunakan Pembangkangan Sipil pada Unjuk Rasa Tolak Kenaikan BBM di Indonesia - Raidah Intizar Yusuf; Andini Hamdi; Rahmah Fitriana (Departement of Communication Sciences, Faculty of Social and Political Sciences, UIM, 2023)
This research aims to analyze the forms of disobedience that occurred in protests against increased fuel prices in September 2022. The study uses qualitative methods such as interviews, news analysis, and literature review to understand how civil disobedience was used by students as a form of political activism. Findings show that the students employed tactics such as road blockades, gas station boycotts, and tanker/truck takeovers as forms of disobedience. These actions align with the principles of prudence, communication, publicity, and non-violence in the theory of civil disobedience. The study concludes that despite the use of civil disobedience, the protests did not lead to policy reform and highlights the need for strong leadership, support, and determination for success in a protest.